Visit-to-Visit Variability in Total Cholesterol Correlates with the Progression of Renal Function Decline in a Chinese Community-Based Hypertensive Population - Yuqin Yan; Yuqin Huang; Dan Zhou; Songtao Tang; Ying-qing Feng (Karger Publishers, 2019)
Background: Studies have demonstrated that cholesterol variability is an independent predictor of cerebrovascular and cardiovascular events. Objective: This study aimed to investigate the association of visit-to-visit variability in total cholesterol (TC) with kidney decline in a Chinese community-based population. Methods: We assessed intraindividual variability in TC among 6,465 hypertensive participants and correlated the results with endpoints. TC variability was measured using standard deviation (SD), average successive variability (ASV), coefficient of variation (CV), and variability independent of the mean (VIM). The endpoint of this study was progression of renal function decline defined as a decrease in estimated glomerular filtration rate (eGFR) ≥30% and to a level <60 mL/min/1.73 m2 during follow-up if the baseline eGFR was ≥60 mL/min/1.73 m2, or a decrease in eGFR ≥50% during follow up if the baseline eGFR was <60 mL/min/1.73 m2. Results: After a median follow-up of 27 months, 13.5% (n = 877) of the participants experienced progression of renal function decline. In the multivariable-adjusted Cox model, each 1-SD increase in TC variability (by SD) increased the risk of renal function decline by 11% (HR = 1.11; 95% CI 1.034-1.197; p = 0.004); this was independent of the baseline eGFR, mean follow-up TC levels, and the lipid-lowering therapy. Similar results were found for the 3 other measures of variability, i.e., ASV, CV, and VIM. Conclusion: In subjects with hypertension, visit-to-visit variability in TC is an independent predictor of renal function decline.